Meningkatkan Pengetahuan dan Perubahan Perilaku Remaja tentang Kesehatan Reproduksi melalui Penyuluhan dan Edukasi di SMK 1 Krian - Selfya Ningrum; Rony Kriswibowo; Putri Ariatna Alia (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
This study aims to improve adolescents' knowledge and behavior regarding reproductive health through counseling and education at SMK 1 Krian. The background highlights the low awareness of reproductive health among Indonesian youth, leading to issues such as unwanted pregnancies and sexually transmitted infections. The counseling program involved 12th-grade students and teachers, utilizing interactive methods to engage participants effectively. Results indicate a significant increase in knowledge, with average scores rising from 55% to 80% post-counseling. Additionally, 70% of students reported positive behavioral changes, such as increased willingness to discuss reproductive health issues. Participant feedback was overwhelmingly positive, with 85% finding the information beneficial. However, challenges remain, particularly regarding access to accurate information. The findings emphasize the necessity for ongoing education and community support to sustain positive changes in adolescents' reproductive health awareness and behavior.